Flash programming for the social & behavioral sciences a simple guide to sophisticated online surveys and experiments - Weinstein, Yana.; DeSoto, K. Andrew; Sage eBooks (Thousand Oaks, [Calif.] ; London : SAGE, 2013)
Adobe Flash is one of the most popular languages for animated web content, and recently social and behavioural scientists have started to take advantage of it to collect data online. This book is a unique, step-by-step guide to using Adobe Flash to develop experiments and other research tools. No previous knowledge of programming is required, though general computer literacy is assumed.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Flash (Computer file); Web sites -- Authoring programs; Internet surveys -- Software; Electronic books